Seasonal evolution and interseasonal changes in polar mesospheric clouds at high latitudes in the Southern Hemisphere. (December 2021) - Solodovnik, A.; Leontyev, P.; Dalin, P.; Takenov, B.; Alyoshin, D.
Abstract: The total areas and other related characteristics of polar mesospheric clouds of the Southern Hemisphere are determined on the basis of the processing of images obtained from the AIM satellite mission. Daily images have been analyzed from 2007 to 2008 to 2019–2020 austral summer seasons. The set of the analyzed data allowed us to study the features of seasonal and inter-seasonal changes in the development of polar mesospheric clouds (PMCs). Long-term temporal changes in such parameters as the maximum and integral areas of the cloud field, the date of the first appearance and disappearance of PMCs, as well as their season durations have been considered in detail. The conclusion about the non-random nature of changes in these characteristics in some seasons is substantiated. It is possible that the PMC evolution is influenced by fluctuations in weather and climatic conditions in the Antarctic region. This assumption is supported by both the relationship between the intensity of mesospheric clouds development in the Southern Hemisphere and variations in seasonal mean (in the context of the clouds existence) temperatures in Antarctica as well as between the stable similarity in seasonal changes in temperature and PMC field areas. Highlights: Satellite images of polar mesospheric clouds in the Southern Hemisphere are analyzed. The non-random nature of inter-seasonal changes in mesospheric cloud fields is shown. A relationship between changes in daily mean temperatures of the troposphere in Antarctica and PMC field areas is revealed.